The progress and prospect of natural components in rhubarb (Rheum ribes L.) in the treatment of renal fibrosis - Wang, Yangyang; Yu, Fangwei; Li, Ao; He, Zijia; Qu, Caiyan; He, Caiying; Ma, Xiao; Zhan, Huakui (Frontiers in Pharmacology, 2022)
Abstract Background: Renal fibrosis is a key pathological change that occurs in almost all chronic kidney disease (CKD) progression. CKD has the characteristics of high morbidity and mortality with its prevalence increasing year by year on a global scale, which seriously affects people's health and quality of life).Natural products have been used for new drug development and disease treatment for many years. The abundant natural products in R. ribes L. can intervene in the process of renal fibrosis in different ways, and have considerable therapeutic prospects. Purpose： The etiology and pathology of renal fibrosis were analyzed, and the natural components of rhubarb in different ways of intervention and curative effects on the process of renal fibrosis were summarized. Methods： Search through electronic databases such as PubMed, Life Science, MEDLINE, and Web of Science using keywords ‘R. ribes L.’, ‘kidney fibrosis’, ‘emodin’ and ‘rhein’, and collect and sort out natural ingredients through various ways to fight against effective ingredients on renal fibrosis. Result： We analyzed several factors that play a leading role in the pathogenesis of renal fibrosis, such as the mechanism of the TGF-β/Smad, Wnt/β-catenin signaling pathway. Also, we reviewed the progress of the treatment of renal fibrosis with natural components in R. ribes L. and the intervention mechanism of crucial therapeutic targets. Conclusions： The natural components of R. ribes L. have a wide range of intervention effects on renal fibrosis targets, which provides new ideas for the development of new anti-kidney fibrosis drugs.